Junior Trainees Group (JTG) of the British Association of Oral and Maxillofacial Surgeons (BAOMS) conference 2018: overview of the conference and analysis of delegates' feedback. Issue 10 (December 2019) - Solanki, K.; Basyuni, S.; Zarringhalam, P.; Nugent, G.; Douglas, J.; Rowe, A.; Magennis, P.
Abstract: The Junior Trainees Group (JTG) of the British Association of Oral and Maxillofacial Surgeons (BAOMS) and the JTG Annual Conference aim to support pre-registrar trainees interested in OMFS. The theme of the 2018 conference, "Research and Innovation" was disseminated through a diversity of expert speakers and interactive workshops. This paper provides an overview of the conference and analysis of the delegates' feedback to show how it represented their interests and influenced their decisions to pursue OMFS. Online questionnaires assessed demographics and the impact of the conference on numerous aspects of the decisions made about careers by delegates at different levels of training. A Kruskal Wallis test with post-hoc pairwise comparisons was done to assess the significance of differences between groups. A total of 135 delegates completed the questionnaires (13% dual-qualified; 13% second-degree medics; 18% second-degree dentists; 6% singly-qualified medics; 41% singly-qualified dentists; 5% first-degree medics; and 4% first-degree dentists), and 141 submitted abstracts of which 32 poster and 12 oral presentations were accepted. A total of 79/135 (59%) were members of the BAOMS. Word-of-mouth was the commonest way by which delegates became aware of the conference. As the stage of training advanced, they agreed more that it represented their training level and influenced them to pursue research and attend the BAOMS 2018 conference. The JTG conference is the only national meeting for pre-registrar trainees, and this year there were record numbers of delegates and abstracts. As the JTG grows, we continue to assist juniors to pursue their involvement in OMFS units and to participate in research and collaborative projects. Our goals are to expand as a national platform to represent junior trainees who are interested in OMFS, and to support them as they progress towards registrar training.